Cooling rates of type I chondrules from Renazzo: Implications for chondrule formation. (15th January 2018) - Chaumard, Noël; Humayun, Munir; Zanda, Brigitte; Hewins, Roger H.
Abstract: Cooling rates are one of the few fundamental constraints on models of chondrule formation. In this study, we used Cu and Ga diffusion profiles in metal grains to determine the cooling rates of type I chondrules in the Renazzo CR2 chondrite. To improve previous estimations of cooling rates obtained using this method, we used CT scanning and serial polishing of our sections to analyze equatorial sections of large metal grains. Through the cores of these metal grains situated at the surface of chondrules, the cooling rates calculated range from 21 to 86 K h −1 for a peak temperature T p 1623–1673 K. A metal grain embedded in the core of a chondrule exhibits a cooling rate of 1.2 K h −1 at a T p 1573 K. We also measured Cu‐Ga diffusion profiles from nonequatorial sections of metal grains and calculated a lower range of cooling rates of 15–69 K h −1 for T p 1473–1603 K compared to our results from equatorial sections. The high cooling rates inferred from the lightning model (several thousand K h −1 ) are clearly at odds with the values obtained in this work. The X‐wind model predicts cooling rates ( 6–10 K h −1 ) lower than most of our results. The cooling rates calculated here are in close agreement with those inferred from shock wave models, in particular for temperatures at which olivine crystallizes (from 10 to several hundreds K h −1 between 1900 and 1500 K). However, the chemical compositions of metal grains in Renazzo are consistent with the splashing model, in which a spray of metal droplets originated from a partially molten planetesimal. Volatile siderophile element depletion is explained by evaporation before metal was engulfed within silicate droplets. Liquid metal isolated from the liquid silicate crystallized during cooling, reacted with the ambient gas, and then re‐accreted within partially molten chondrules.